2018
DOI: 10.1016/j.ultrasmedbio.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Contrast-Enhanced Ultrasound Versus Conventional Ultrasound for Differentiation of Benign and Malignant Breast Lesions

Abstract: This meta-analysis aimed to compare the diagnostic performance of contrast-enhanced ultrasound (CEUS), conventional ultrasound (US) combined with CEUS (US + CEUS) and US for distinguishing breast lesions. From thorough literature research, studies that compared the diagnostic performance of CEUS versus US or US + CEUS versus US, using pathology results as the gold standard, were included. A total of 10 studies were included, of which 9 compared the diagnostic performance of CEUS and US, and 5 studies compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 35 publications
5
30
1
Order By: Relevance
“…For m-US, we found a sensitivity of 88.9% and a specificity of 86.4% which is within the range of previously reported values [18][19][20][21]. A recent meta-analysis [22] published a sensitivity of 87% and specificity of 72%. It is noteworthy that for r-US, we observed an equally high sensitivity, while the specificity was slightly higher than for m-US (89.4% versus 86.4%).…”
Section: Discussionsupporting
confidence: 88%
“…For m-US, we found a sensitivity of 88.9% and a specificity of 86.4% which is within the range of previously reported values [18][19][20][21]. A recent meta-analysis [22] published a sensitivity of 87% and specificity of 72%. It is noteworthy that for r-US, we observed an equally high sensitivity, while the specificity was slightly higher than for m-US (89.4% versus 86.4%).…”
Section: Discussionsupporting
confidence: 88%
“…Sensitivity was similar to that reported by a meta-analysis of studies of CEUS, with 86% sensitivity, but the specificity was lower than in the meta-analysis (79%) 22. Similar observation can be made with B-mode ultrasound (87% sensitivity and 72% specificity) 23. This could possibly be due to differences in image analysis and may suggest that our classification method could be improved.…”
Section: Discussionsupporting
confidence: 86%
“…In a meta‐analysis from 2016 that included 2296 lesions, Ma et al showed that CEUS could potentially be an effective tool in differentiating benign from malignant breast lesions. In a meta‐analysis from 2018 encompassing 2568 breast lesions, Li et al concluded that CEUS alone and CEUS with conventional US had better diagnostic performance than conventional US alone. Both quantitative and qualitative CEUS parameters have been useful in distinguishing benign and malignant masses.…”
Section: Discussionmentioning
confidence: 99%